Upper airway and hyoid bone-related morphological parameters associated with the apnea-hypopnea index and lowest nocturnal oxygen saturation: a cephalometric analysis - Zhili Dong; Yue Zeng; Jieyi Chen; Liping Wu; Hong Hong (BMC Oral Health)
Abstract Background Obstructive sleep apnea (OSA) is a common disorder characterized by repetitive complete or partial closure of the upper airway during sleep, resulting in sleep fragmentation and oxygen desaturation. Cephalogram is recognized as an effective diagnostic tool for predicting OSA risk in clinical practice. This study aims to assess and analyze the morphological characteristics of the upper airway and hyoid bone position associated with OSA using data from polysomnography studies and two-dimensional cephalometric analysis. Methods The study included lateral cephalograms and polysomnography reports from the records of 105 adult (64 males & 41 females) patients who underwent comprehensive clinical examination. The severity of OSA was evaluated based on the apnea-hypopnea index (AHI) and lowest nocturnal oxygen saturation (LSaO2). The participants were divided into male and female groups to investigate the correlation between cephalometric parameters and OSA severity. Thirteen cephalometric parameters, including eleven linear measurements and two angular measurements, were analyzed. The significance level was set at P-value < 0.05. Results The male group exhibited significantly higher severity of OSA compared to the female group, as indicated by higher AHI and lower LSaO2. There was an inverse association between AHI values with width of upper airway as well as distance between hyoid bone position relative to mandibular plane in both male and female groups. Additionally, only the male group showed a correlation between hyoid bone position relative to gonion/third-fourth vertebrae positions with AHI values. 4 out of 7 parameters associated with AHI in male group remained correlated with LSaO2, while in females only the distance between hyoid bone and line formed by ptergoid and pterygomaxillary fissure point showed correlation with LSaO2. Conclusion Correlation analysis revealed that a narrower upper airway was positively associated with increased AHI, while an inferiorly positioned hyoid bone in relation to mandible was negatively correlated with LSaO2. Our findings highlight the importance of several cephalometric parameters in predicting OSA severity based on AHI and LSaO2 levels; moreover, certain parameters exhibited significant gender-specific associations.